PENGARUH PEMBERIAN MEDIA BOOKLET SADARI TERHADAP TINGKAT PENGETAHUAN REMAJA PUTRI DI SMA NEGERI 1 LOSARI CIREBON - Shelvi Yolandina; Wijayanti; Dheny Rohmatika (Jurnal Ilmu Kebidanan, 2023)
Breast cancer is the type of cancer that ranks first with the highest number, and is one of the highest contributors to cancer deaths. This study aims to determine the effect of giving SADARI booklet media on the level of knowledge of adolescent girls at SMA Negeri 1 Losari Cirebon. Methods: This study used a pseudo-experiment and a nonequivalent control group design. The sample amounted to 74 respondents, with proportional random sampling technique. Results: Based on the results of the characteristics of research respondents in the experimental group as many as 33 respondents have never received information about SADARI, while in the control group as many as 35 respondents. Univariate analysis was carried out, the pretest of the experimental group had an average value of 12.00 and the control group was 12.14. After being given action in the experimental group using the SADARI booklet, a posttest was carried out with an average value of 14.84, while the control group used a lecture on SADARI, with an average of 12.46. Normality test was conducted using Kolmogorov Smirnov with the results of normally distributed data. And the Levene test was carried out with the results of homogeneous data. Furthermore, bivariate tests were carried out, using a paired T-test, with a sig value. (0,000). Based on the results of the study, it was concluded that there were differences in the level of knowledge of adolescent girls at SMA Negeri 1 Losari Cirebon before and after being given learning through the SADARI booklet media.